Multi-constrained trusted cooperative task migration strategy for edge computing - Guangxue YUE; Yasheng DAI; Xiaohui YANG; Youkang ZHU; Zhenxu YOU; Jiansheng LIU (Dianxin kexue)
In order to guarantee the quality of service of edge computing,a trusted cooperative task distribution strategy for edge computing under multi-dimensional constraints was proposed.The strategy was based on the task requirements,and the edge computing collaborative service leader node organizes the coordinated service alliance members.The priority of cooperative service alliance was determined based on the K-dimension weight index of user task migration.Using the load balancing of the members as the adaptive function,the task allocation and dispatch of alliance members were performed by greedy algorithm.The backup node was selected based on routing piggyback,and the priority of migration was evaluated.The scheduling and migration of collaborative services in case of abnormal collaborative services were realized,which improved the quality of service of edge computing task migration and ensured the reliability of task migration.The simulation results show that the mechanism can effectively complete the task distribution and migration scheduling,improve the collaborative efficiency of edge computing,and guarantee the quality of network service.